Beyond the person: the construction and transformation of blood as a resource. Issue 3 (27th May 2017) - Lynch, Rebecca; Cohn, Simon
Abstract: Many studies of blood donation have looked at the motives of donors, their relationship with the wider society and corresponding values such as gift-giving, altruism and responsibility. These underpin a rhetorical representation of person-to-person donation that neglects the many technical processes that take place between donation and eventual use and the material nature of blood itself. This ethnographic study, conducted in four UK blood donation sites, describes the various practices involved in routine sessions, rather than the motives or values or donors or staff. It focuses on the procedures and equipment that not only ensures blood is collected safely and efficiently, but the extent to which they determine the nature of the collected blood itself. Taking our cue from posthuman approaches, we argue donated blood as something that is 'made' only when it leaves the body; in other words, it is not simply extracted, but is constructed through specific practices. We illustrate how, as blood is separated from the body, it is increasingly depersonalised and reconstituted in order to have biomedical value. In this way, rather than reproducing the essentialist claim that blood is what social scientists often described as a 'special kind of substance', we point to the ways in which donated blood alters as it moves in time and space. We argue that such transformations occur in both symbolic and material realms, such that the capacity of blood to have both cultural meaning and clinical value is dependent on the fact that it is never stable or singular.